Functional Maintenance of Differentiated Embryoid Bodies in Microfluidic Systems: A Platform for Personalized Medicine. (9th February 2015) - Guven, Sinan; Lindsey, Jennifer S.; Poudel, Ishwari; Chinthala, Sireesha; Nickerson, Michael D.; Gerami-Naini, Behzad; Gurkan, Umut A.; Anchan, Raymond M.; Demirci, Utkan
Abstract : The utility and advantage of a microfluidic chip culture system to enhance the development of personalized, on-demand, treatment modules using embryoid bodies (EBs) is demonstrated. Under microfluidic conditions, differentiated steroidogenic EBs continued to secrete estradiol and progesterone at physiologically relevant concentrations. These results present a platform for the development of a new therapeutic system for personalized medicine. Abstract: : Hormone replacement therapies have become important for treating diseases such as premature ovarian failure or menopausal complications. The clinical use of bioidentical hormones might significantly reduce some of the potential risks reportedly associated with the use of synthetic hormones. In the present study, we demonstrate the utility and advantage of a microfluidic chip culture system to enhance the development of personalized, on-demand, treatment modules using embryoid bodies (EBs). Functional EBs cultured on microfluidic chips represent a platform for personalized, patient-specific treatment cassettes that can be cryopreserved until required for treatment. We assessed the viability, differentiation, and functionality of EBs cultured and cryopreserved in this system. During extended microfluidic culture, estradiol, progesterone, testosterone, and anti-müllerian hormone levels were measured, and the expression of differentiated steroidogenic cells was confirmed by immunocytochemistry assay for the ovarian tissue markers anti-müllerian hormone receptor type II, follicle-stimulating hormone receptor, and inhibin β-A and the estrogen biosynthesis enzyme aromatase. Our studies showed that under microfluidic conditions, differentiated steroidogenic EBs continued to secrete estradiol and progesterone at physiologically relevant concentrations (30–120 pg/ml and 150–450 pg/ml, respectively) for up to 21 days. Collectively, we have demonstrated for the first time the feasibility of using a microfluidic chip system with continuous flow for the differentiation and extended culture of functional steroidogenic stem cell-derived EBs, the differentiation of EBs into cells expressing ovarian antigens in a microfluidic system, and the ability to cryopreserve this system with restoration of growth and functionality on thawing. These results present a platform for the development of a new therapeutic system for personalized medicine.